PENGARUH PEMBERIAN SUSU KEDELAI TERHADAP TEKANAN DARAH PASIEN HIPERTENSI DI WILAYAH PUSKESMAS GARUDA KECAMATAN MARPOYAN DAMAI - Santi Widiasari; Ilham Aditya Putra (Collaborative Medical Journal, 2022)
Hypertension is a health problem which one of the main concerns even in worldwide since this disease is a significant risk factor that leads to cardiovascular diseases such as heart attack, heart failure, stroke, and kidney disease. Hypertension is divided into two types based on the cause, primary hypertension and secondary hypertension. Some treatments that help lower blood pressure are by using drugs (pharmacotherapy) or by way of lifestyle modifications. Soybean (Glycine Max) is a type of functional food that contains nutrients such as isoflavones, saponins, lecithin and phytosterols which reduce the risk of cardiovascular disease. This study aims to analyze the effect of giving soy milk on blood pressure in hypertensive patients. This research method used a pretest-posttest design with a control group design. The sample in this study used a purposive sampling technique, the maximum size of the subjects in the study was 30 people. The results of the study in the intervention group showed that there was an effect of giving soy milk on blood pressure in hypertensive patients before and after with systolic blood pressure p=0.000 (p<0.05) and diastolic blood pressure p=0.002 (p<0.05).